If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -89 = 176 Reorder the terms: -89 + x = 176 Solving -89 + x = 176 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '89' to each side of the equation. -89 + 89 + x = 176 + 89 Combine like terms: -89 + 89 = 0 0 + x = 176 + 89 x = 176 + 89 Combine like terms: 176 + 89 = 265 x = 265 Simplifying x = 265
| 2q-5=8q+1 | | X+52+90+90=360 | | x^2-X=43.32 | | 40=-5m-5 | | 64+x=146 | | X=25+24 | | 2m^(3)n^(6)/10m^(2)n^(3) | | -3x+51+15x=3 | | 14+r=26 | | X=17+4 | | x^2+10x+18=x | | 4(3n-1.2)-0.5=9.5+0.2 | | x+77=394 | | X=29-9 | | 25x-20=15x+15 | | 4d+13-6-13.20= | | 45=3s | | 2x+3y=1700 | | 25=17+m | | X=28+22 | | 3d+13-6-13.20=1.55 | | X=21+11 | | 3d+13-6-13.20=1.60 | | 128+x+40+82=360 | | x+5.25=7.55 | | X=19+11 | | 3d+13-6-13.20=2.07 | | X=28+14 | | 6=1.2 | | s-3.2=6 | | X=19+13 | | X=25+17 |